Increasing global mortality from idiopathic pulmonary fibrosis in the twenty-first century - Hutchinson, John P.; McKeever, Tricia M.; Fogarty, Andrew W.; Navaratnam, Vidya; Hubbard, Richard B. (American Thoracic Society, 2014)
Rationale: Recent evidence from the United Kingdom suggests that the number of deaths from idiopathic pulmonary fibrosis is increasing, although comparable international data are limited.